Numerical Scheme for Solving Singular Two-Point Boundary Value Problems - N. Ratib Anakira; A. K. Alomari; I. Hashim (Journal of Applied Mathematics)
Singular two-point boundary value problems (BVPs) are investigated using a new technique, namely, optimal homotopy asymptotic method (OHAM). OHAM provides a convenient way of controlling the convergence region and it does not need to identify an auxiliary parameter. The effectiveness of the method is investigated by comparing the results obtained with the exact solution, which proves the reliability of the method.